Constitutive relations of coral aggregate concrete under uniaxial and triaxial compression. (10th August 2020) - Zhou, Wen; Feng, Peng; Lin, Hongwei
Highlights: Porous and low strength nature of coral result in special properties of CAC. Constitutive models were suggested for CAC under uniaxial and triaxial compression. A failure criterion for LAC was proved to be applicable to CAC under compression. Abstract: Coral aggregates can replace natural aggregates in marine construction, substantially reducing construction costs and shortening construction period. This paper investigates the compression behavior of coral aggregate concrete (CAC) under uniaxial and triaxial loading, wherein lightweight aggregate concrete (LAC) and normal aggregate concrete (NAC) are used for comparison. The investigated variables include concrete type, concrete strength, lateral pressure and principal stress ratios. The results indicated that the compression behaviors of CAC were different from those of NAC but similar to those of LAC because coral aggregates are more porous and have lower strength than normal aggregates. Based on the test results from this paper and literature studies, constitutive models were suggested for CAC under uniaxial and conventional triaxial compression. Moreover, a failure criterion for LAC proposed in the literature was deemed applicable to CAC under active or passive confinement. The suggested models correlated well with the test results.